2016
DOI: 10.3174/ajnr.a4824
|View full text |Cite
|
Sign up to set email alerts
|

Regional Frontal Perfusion Deficits in Relapsing-Remitting Multiple Sclerosis with Cognitive Decline

Abstract: Background and Purpose Cortical dysfunction, quantifiable by cerebral perfusion techniques, is prevalent in MS patients contributing to cognitive impairment. We sought to localize perfusion distribution differences in relapsing-remitting MS patients with and without cognitive impairment, and healthy controls. Materials and Methods 39 relapsing-remitting MS patients (20 cognitively impaired, 19 non-impaired) and 19 age and gender-matched healthy controls underwent a neurocognitive battery and MRI scanning. Vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…[ 34 , 35 ] A previous study reported a significant hypoperfusion area was found for MS in the superior frontal gyrus, suggesting superior frontal gyrus has tissue damage. [ 36 ] The similar alteration was also reported in other previous perfusion study, [ 37 ] which showed a progressive cerebral blood flow and cerebral blood volume deficits present in the superior frontal gyrus for RRMS patients. Another study using echo planar spectroscopic imaging showed abnormal metabolite such as decreased NAA and Glx were predominantly tested in gray matter within prefrontal cortices in MS patients.…”
Section: Discussionsupporting
confidence: 85%
“…[ 34 , 35 ] A previous study reported a significant hypoperfusion area was found for MS in the superior frontal gyrus, suggesting superior frontal gyrus has tissue damage. [ 36 ] The similar alteration was also reported in other previous perfusion study, [ 37 ] which showed a progressive cerebral blood flow and cerebral blood volume deficits present in the superior frontal gyrus for RRMS patients. Another study using echo planar spectroscopic imaging showed abnormal metabolite such as decreased NAA and Glx were predominantly tested in gray matter within prefrontal cortices in MS patients.…”
Section: Discussionsupporting
confidence: 85%
“…36,37 The enrichment of genes associated with multiple sclerosis in the inferior frontal gyrus might explain reductions in blood flow and activation correlated with cognitive impairments in affected patients. 38,39 Lastly, the enrichment of genes associated with neuralgia and migraine in the midcingulate cortex is in accordance with a recently characterized pathway from the area to the posterior insula that supports the development of chronic hypersensitivity to pain. 40 Limitations arising from different sources need to be considered.…”
Section: Discussionsupporting
confidence: 80%
“…In similar manner, hypoperfusion of the thalamus, a deep gray matter (DGM) region highly implicated in MS, has been associated with worse disability and composite clinical scores (8). Lastly, MS patients with cognitive impairment demonstrate greater cortical perfusion deficits despite any evidence of structural abnormalities or significant brain atrophy (9). The changes in DSC and ASL-based perfusion measures within the cortical and DGM in MS patients and their association with clinical outcomes have been recently reviewed elsewhere (6).…”
Section: Introductionmentioning
confidence: 98%